No evidence for generational differences in the conventionalisation of face emojis - Vera Kempe; Limor Raviv (Computers in Human Behavior Reports)
Despite strong popular beliefs that older users misunderstand emojis, empirical evidence is equivocal. Here we propose that different generations of users may vary in the degree of intra-generational agreement on emoji meanings (i.e., how much people from the same generation agree on what an emoji means). Inspired by research in cultural evolution demonstrating a positive association between social network size and the conventionalisation of signs, we hypothesised that younger users would show stronger agreement on emoji meanings because they tend to be embedded in larger online social networks than older users. We examined generational differences in intra-generational agreement on emoji interpretations, taking into account variability arising from different emoji renderings across platforms. In a pre-registered online study, 394 respondents from the culturally defined generations of GenZ (n = 152, age 13–24 years), Millennials (n = 149, age 25–40 years), and GenX/BabyBoomers (n = 93, age 41–76 years) produced three words to describe the meanings of 24 target face emojis and 10 popular filler emojis. Frequentist and Bayesian analyses showed no generational differences in intra-generational response entropy and in the probability of selecting the most frequent meaning within one's generation. Exploratory analysis further showed that the most commonly provided emoji interpretations did not differ across generations, despite generational differences in social media usage patterns. Together, these findings suggest that different generations not only interpret face emojis in similar ways, but also show similar intra-generational agreement on emoji meanings, consistent with the idea that, after a decade of use, face emojis have become a widely conventionalised semiotic system accessible to digital media users regardless of age.